Obsessive Love Disorder Portrayed Through Male Main Character in Ana Huang's Twisted Lies Novel - Amalia, Alvia (EDUJ : English Education Journal, 2024)
This thesis analyze the obsessive love disorder experienced by Christian Harper, the male main character in Ana Huang's novel, Twisted Lies. The objectives of this thesis are to know the symptoms of obsessive-love, the causes of the obsessive-love and the effects of obsessive-love in Ana Huang's Twisted Lies novel. The writer uses descriptive qualitative method. To analyze the novel the writer read the novel several times and uses theories from books and journal. The result of this study are the symptoms of male main character having obsessive love disorder are making Stella his idealized lover, delusional jealousy, and pursuit. The causes of male main character having obsessive love disorder is abandonment. Meanwhile, the effects of male main character having obsessive love disorder is isolation.